50 things to know about the International Space Station - Read, John A. (Formac Publishing Company Limited, 2021)
Presents fifty illustrated facts about the International Space Station pertaining to its construction, astronauts, space experiments, and daily operations. Includes color photographs, a glossary, appendixes, and further resources.